Factors and determinants of value- and business-driven sustainability initiatives in health care organizations: intrinsic differences and extrinsic similarities. Issue 4 (5th August 2019) - Rodriguez, Rocio; Svensson, Göran; Høgevold, Nils M.; Eriksson, David
Abstract : Purpose: The purpose of this paper is to compare the similarities and differences relating to sustainability initiatives between health-care organizations. The aim is to provide a framework of factors and their determinants to enable a profiling of organizational sustainability initiatives. Design/methodology/approach: Based on an inductive approach, judgmental sampling was applied to select relevant health-care organizations. Informants were identified according to their knowledge of their organizations' sustainability initiatives. Findings: Several factors and their determinants for characterizing differences and similarities were found. The results also reveal that organizational sustainability initiatives are either value-driven or business-driven. Research limitations/implications: The reported framework of factors and their determinants serves the purpose of profiling organizational sustainability initiatives. Opportunities for further research are provided. Practical implications: This paper provides managerial guidance for characterizing the differences and similarities with respect to organizational sustainability initiatives in relation to other organizations. Originality/value: This study establishes a framework for characterizing organizational sustainability initiatives. It also contributes to reveal whether organizational sustainability initiatives are value – or business-driven and considers intrinsic-oriented differences and extrinsic-oriented similarities.